Uji Kadar Flavonoid Dan Aktivitas Antioksidan Pada Ekstrak Kulit Buah Melinjo (Gnetum Gnemon L) - Fadhlurrahman Fadhlurrahman; Halim Zaini; Ratni Dewi (Politeknik Negeri Lhokseumawe, 2025)
Melinjo fruit peel waste has various components or compounds that function for the body and can be used for natural food coloring. The compounds found in red melinjo fruit peel are phenolics, flavonoids, lycopene, vitamin C, and Î²-carotene. The objective of this study was to determine the effect of variations in extraction time and solvent type on flavonoid content and antioxidant activity. This study was conducted by varying the maceration extraction time for 1, 2, 3, 4 and 5 days, the types of solvents used were distilled water and 70% ethanol. The results of melinjo fruit peel extract on the effect of extraction time on both solvents, the longer the extraction time, the better the results. Depending on the type of solvent used, the 70% ethanol solvent produces a more complex extract because ethanol is active in the extraction of flavonoids, and the Aquadest solvent can only extract components that are only soluble in water. The effect of varying the extraction time using the solvent types of distilled water and 70% ethanol on the flavonoid content test showed a maximum increase in flavonoid levels on day 5. And in the antioxidant activity test, the effect of extraction time shows that the longer the extraction the higher the %inhibition, the type of 70% ethanol solvent produces an antioxidant value of 2.42 Î¼g/mL, which is more effective to use because it produces a higher %inhibition compared to Aquadest solvent with a value of 5.45 Î¼g/mL.